Come la modernità dimentica: interventi urbani e pratiche d'archivio come antidoti all’oblio nella ricerca artistica contemporanea - Paola Valenti (Annali Online dell'Università di Ferrara. Sezione Lettere)
Taking Paul Connerton’s essay How modernity forgets (2009) as a starting point and using it as a fil rouge in the argumentation, the paper aims to reflect on how the transformations impressed in the social fabric and in the public space by capitalism affect our capacity to remember, generating a “culture of oblivion”. In the last decades, and especially after 1989, as the new political and social asset of the world gave rise to a resilient need of recollecting national memories and identities, this issue has become more and more important in the artistic research. In this context many international artists work with the aim of encouraging a recovery of a “cultural memory”: some of them undertake actions or walks (often involving the public) in the urban space to let re-emerge the histories or cultural identities of significant places (as in the cases, token into account in the essay, of Gregor Schneider, Luca Vitone and Cesare Viel); other ones (John Akomfrah and Walid Raad) trick or forge the archive in order to excavate stories that have been overwhelmed by the “dominant narrative”.